Kompresi toraks fatal akibat lipoma abdomen dan distensi lambung pada kucing - Anugerah, Cahya Alamsyah Putra; Salsabila, Cut Aja; Febryawan, Ghazy Zhafran; Khairani, Shafia (ARSHI Veterinary Letters, 2025)
Respiratory distress due to abdominal pathology presents a diagnostic challenge in small animal practice and may be fatal if not promptly recognized. This case study describes the pathological findings in a domestic cat with thoracic cavity narrowing secondary to severe gastric distension and an abdominal lipoma. Necropsy was performed on a cat with dyspnea, abdominal pain, gait incoordination, and influenza-like symptoms. Postmortem examination revealed multiple pathological lesions, including marked gastric distension due to gas accumulation, a solitary lipoma within the abdominal cavity, gastritis, enteritis, Ascaris spp. infection (ascariasis), pulmonary hemorrhage, and tracheal hyperemia. The concurrent presence of abdominal lipoma and gastric distension likely exerts mechanical pressure on the diaphragm and thoracic cavity, restricting lung expansion and impairing gas exchange. This pressure-induced respiratory compromise is considered the primary factor for animal death. This report emphasizes the need for thorough clinical evaluation in cases with respiratory and abdominal signs, highlighting how abdominal masses can trigger life-threatening complications.